2011
DOI: 10.1083/jcb.201106149
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 regulates the localization and activity of Eg5 in the mammalian mitotic spindle

Abstract: TPX2 promotes mitotic spindle formation by enhancing Eg5 accumulation on microtubules and limiting motor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 42 publications
13
128
0
Order By: Relevance
“…2d). In addition, cells where Eg5 is overactive often undergo multipolar mitosis 18 . Second, Eg5 carries several putative KEN 19 and D-box 20 motifs at the C-terminal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2d). In addition, cells where Eg5 is overactive often undergo multipolar mitosis 18 . Second, Eg5 carries several putative KEN 19 and D-box 20 motifs at the C-terminal.…”
Section: Resultsmentioning
confidence: 99%
“…Here we show that Eg5 stabilization by selective inhibition of APC/C-CDH1 is sufficient to kill CA cells, suggesting that selective targeting of APC/C-CDH1 may represent an effective therapeutic approach in CA tumours. In addition, it has been shown that TPX2 acts as a brake on Eg5 motor, and that knockdown of TPX2 results in increased Eg5 activity and multipolar spindles in cancer cells 18 . It is plausible that any therapeutic approach aimed to increase outward forces on the mitotic spindle could effectively kill tumours with CA.…”
Section: Ub-eg5mentioning
confidence: 99%
“…In somatic cells (Ma et al, 2011), upon binding a microtubule-binding protein called TPX2, AURKA auto-activates and regulates the building of the bipolar spindle by recruiting other PCM proteins, promoting microtubule nucleation and anti-parallel sliding forces, and maintaining the integrity of astral microtubules with the cortex (Dodson and Bayliss, 2012;Giubettini et al, 2011;Kufer et al, 2002;Li et al, 2008;Scrofani et al, 2015). In mouse oocytes, overexpression of AURKA increases MTOC numbers prematurely (Saskova et al, 2008;Solc et al, 2012), and its depletion causes disorganized meiosis I spindles (Saskova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that while the interaction of TPX2 with Aurora‐A is crucial for controlling spindle length (Fig 5), the interactions of TPX2 with ADD1 and Eg5 are essential for spindle pole integrity (Figs 5 and 6). TPX2 has been shown to bind Eg5 and suppress its motor activity during mitosis, which ensures proper bipolar spindle formation 25. Interestingly, we found that the multipolar spindles and centriole splitting induced by ADD1 depletion were Eg5‐dependent (Fig 7), rendering it possible that ADD1 binding may be necessary for TPX2 to interact with Eg5 and/or suppress Eg5 activity.…”
Section: Discussionmentioning
confidence: 79%